Young adults without a vocational qualification – unused skilled worker potential? - Kalinowski, Michael [Verfasser] (My University, 2026)
"n 2023, the number of young adults aged from 20 to 34 without a vocational qualification reached a new record high of 2.79 million people. In 2024, the figure decreased for the first time in nine years. This development is presented below, and the explanation of the results is differentiated according to school and vocational qualifications. It is also worth looking at the labour market situation of young adults in order to identify skilled worker potential." (BIBB-Doku)
Keywords: P 2.2 An- und Ungelernte; P 1.5 Migranten; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; 370; Nicht formal Qualifizierter; Jugendlicher ohne Berufsabschluss; Ungelernter; Ausländer; Erwerbsbeteiligung